Technology and accessibility: creation of the children’s audiobook “I want to see the real iemanjá” - Anastácio , Sílvia Maria Guerra; Rocha, Ricardo Oliveira (Farol, 2024)
The purpose of this article is to analyze the process of transposing the children's story “Quero ver a Iemanjá de Verdade” into an audiobook, which is part of the book Minhas Histórias com Belinha. The focus is to analyze the process of creating two scripts based on the aforementioned short story: the first is the script for a radio play for an audiobook; the second is an audio description script of illustrations from the story, which will be recorded as a supplement to the radio play. For the theoretical-critical basis of the analysis, the following material was relevant: Comparato (2018) on script construction; Street (2006), Sperber (1980) and Huwiler (2010) about a radio play; Bolter and Grusin (2000), Elleström (2010) on media studies; Hayles (2004), De Arzabal (2021) and de Gumbrecht (2004) on materiality.